Dwelling Models of Umayyad Mada'in and Qusur in Greater Syria, by Giuseppe Labisi. - Mokránová, Katarína (Journal of Islamic Archaeology, 2021)
Dwelling Models of Umayyad Mada'in and Qusur in Greater Syria, by Giuseppe Labisi. BAR Publishing, 2020. 352pp., with 7 tables and 69 figures, Sc. £74.00. ISBN-13: 9781407357225.